The Model of Associations Between Self-Assessed Critical Thinking Skills, Their Perceived Importance and Work Engagement - Diržytė , Aistė; Sadauskas, Justinas; Indrašienė , Valdonė; Jegelevičienė, Violeta; Merfeldaitė , Odeta; Penkauskienė , Daiva; Pivorienė , Jolanta; Railienė , Asta (Social Welfare: Interdisciplinary Approach, 2025)
he purpose of this study was to explore the links between the perceived importance of critical thinking skills, self-reported critical thinking skills, and work engagement. The study applied a cross-sectional design, and the sample consisted of 2012 employees; the mean age was 41.93 (SD=11.42). To analyse the links between the constructs, three instruments were used: The Work Engagement Scale (UWES), The Perceived Importance of the Critical Thinking Skills Scale (PICTS), and The self-reported Critical Thinking Skills Scale (CTS). For the statistical analyses, SPSS v.26.0, AMOS v.26.0, JASP v.18, and JAMOVI v.2.2.1 software was applied. Confirmatory factor analyses showed the acceptable model fit and validity of the scales in the Lithuanian population. The structural equation modelling results revealed the complex model of the links between the perceived importance of critical thinking skills, the self-reported critical thinking skills, and the elements of work engagement, namely, vigour, dedication, and absorption. The findings revealed that both self-reported critical thinking and the perceived importance of critical thinking skills positively contributed to work engagement, thus indicating the need to foster critical thinking in organizations so that to ensure their flourishing and efficacy.